Advances in the treatment of Benign Prostatic Hyperplasia: An integrative review (Research, Society and Development, 2024)
The condition known as benign prostatic hyperplasia (BPH) is a common occurrence in older men, characterized by the benign enlargement of the prostate, which can lead to bothersome urinary symptoms and significantly affect quality of life. BPH is a significant health concern worldwide, affecting the majority of older men to varying degrees. Although not fatal in itself, it can cause serious complications if not properly treated. Treatment for benign prostatic hyperplasia aims to alleviate symptoms, improve urinary function, and reduce the risk of associated complications. There are various treatment options available, ranging from non-invasive interventions to more complex surgical procedures, depending on the severity of symptoms and patient preferences. To initiate the review process, a search was conducted in the PubMed electronic database with the aim of identifying studies published in the last 3 years (2021 to 2024) that addressed advances in BPH treatment. The specific MESH descriptors used were "Benign Prostatic Hyperplasia", "Treatment", "Therapeutics", "Drug therapy". These terms were selected to ensure the inclusion of studies addressing different aspects related to BPH treatment, from new therapies to management guidelines and future predictions. The results of this review highlight the effectiveness of non-invasive interventions, such as lifestyle modifications and medication therapies, in improving urinary symptoms and quality of life in patients with mild to moderate BPH.